Avaliação do efeito do tempo de desossa sobre a qualidade da carne de peito de matrizes pesadas de descarte - Sanfelice, Cristiane [UNESP]; Mendes, Ariel Antonio [UNESP]; Komiyama, Claudia Marie [UNESP]; Cañizares, Marleide Costa; Rodrigues, Luciana [UNESP]; Cañizares, Gil Ignacio Lara [UNESP] (Universidade Estadual de Maringa, 2010)
The aim of this study was to evaluate the effect of deboning time on broiler breeder hen meat for in natura consumption. Eighty samples of breast fillets with bone (Pectoralis major muscle) were collected and divided into four groups of 20 samples each; each group represented a different post-mortem deboning time: 0 (immediately after cooling), 4, 8 and 12h post-mortem. At 24h post-mortem, all samples were evaluated for the following parameters: pH, color (L*, a* and b*), cooking loss, water retention capacity, shear force, myofibrillar fragmentation index and fiber diameter. Color (L*, a* and b*), cooking loss, water retention capacity and shear force were significantly different (p ≥ 0.05) among the evaluated deboning times. The shear force value of breast fillets deboned at 0h post-mortem (8.478) was significantly different (p ≥ 0.05) from those deboned at 4, 8 and 12h post-mortem (5.154; 5.375 and 4.819, respectively). Therefore, an increase in the tenderness of breast fillets was observed, when deboning was performed at least 4h post-mortem.
Evaluation of deboning time effect on the breast meat quality of spent hen
Keywords: Muscle fiber; Spent hen; Tenderness